Magia rewitalizacji w dobie niepokojącej nowoczesności = Magic of Revitalization in the Age of Disturbing Modernity - Radziewicz-Winnicki, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper attempts to analyze the processes related to methodological, intellectual and cultural tradition of such notions as magic and revitalization occurring in social sciences in the XXI century with reference to some possible conditions. Many disciplines should pay attention to the processes connected with modernization of social structures through the use of the contents included in this article. In particular, economic and cultural determinants of selected issues and the direction of the transformation that occur in Polish democratic and normative order of post-monocentric society are criticized not only by the author but also university professors, lecturers and students. However, at the end of the paper, the author remains optimistic about the valorization of the issues raised above and the application of the magic of revitalization in Poland and in the postindustrial world.
Keywords: magia; rewitalizacja; niepokojąca nowoczesność; magic; revitalization; anxieties of modernity